DELAYED RECOVERY AFTER GENERAL ANESTHESIA AND THE ROLE OF THE ANESTHESIOLOGIST IN ITS MANAGEMENT - Gulzar Baxitboyevna Khashimova; Zebo Yusupovna Madaminova; Yokitjon Shavkatovna Kodirova (Science, education, innovation: modern tasks and prospects, 2025)
This article discusses the causes and consequences of delayed recovery after general anesthesia, as well as the crucial role of the anesthesiologist in managing this condition. Various clinical factors, including patient health status, type of anesthetic drugs used, and surgical complications, are considered. The article also highlights the importance of early diagnosis, patient monitoring, and proper postoperative care to ensure full recovery. It emphasizes how the anesthesiologist can reduce risks and improve patient safety by taking timely and professional actions.